Stability and Hopf Bifurcation of a Computer Virus Model with Infection Delay and Recovery Delay - Haitao Song; Qiaochu Wang; Weihua Jiang (Journal of Applied Mathematics)
A computer virus model with infection delay and recovery delay is considered. The sufficient conditions for the global stability of the virus infection equilibrium are established. We show that the time delay can destabilize the virus infection equilibrium and give rise to Hopf bifurcations and stable periodic orbits. By the normal form and center manifold theory, the direction of the Hopf bifurcation and stability of the bifurcating periodic orbits are determined. Numerical simulations are provided to support our theoretical conclusions.